2016
DOI: 10.15585/mmwr.mm6531a3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of National Public Health Department Accreditation ― United States, 2016

Abstract: In 2011, the nonprofit Public Health Accreditation Board (PHAB) launched the national, voluntary public health accreditation program for state, tribal, local, and territorial public health departments. As of May 2016, 134 health departments have achieved 5-year accreditation through PHAB and 176 more have begun the formal process of pursuing accreditation. In addition, Florida, a centralized state in which the employees of all 67 local health departments are employees of the state, achieved accreditation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…The vision of ensuring that every community is protected by an accredited local or a state health department (or both) requires major investment and political will to enhance existing infrastructure. Although research found accreditation supports health departments in quality improvement and enhancing capacity (20), the health impact and return on investment of accreditation should be evaluated on an ongoing basis.…”
Section: Recommendations To Achieve Public Health 30mentioning
confidence: 99%
“…The vision of ensuring that every community is protected by an accredited local or a state health department (or both) requires major investment and political will to enhance existing infrastructure. Although research found accreditation supports health departments in quality improvement and enhancing capacity (20), the health impact and return on investment of accreditation should be evaluated on an ongoing basis.…”
Section: Recommendations To Achieve Public Health 30mentioning
confidence: 99%
“…Also, comparisons between results of this study and previous, as well as future, studies may be made with caution due to increasing awareness and acceptance of accreditation, broader attention to PHAB requirements, and growing body of evidence about accreditation benefits. 1 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 All state, tribal, local, and territorial health departments are eligible for accreditation, although the majority of participation to date has been among local and state health departments. Accreditation involvement among the nation’s diverse local health departments (LHDs) is especially interesting to assess, as it offers opportunities for analyzing the many factors at play that determine LHD accreditation activities.…”
mentioning
confidence: 99%
See 2 more Smart Citations